417PClinicopathological profile and survival outcomes of sarcomas from a regional cancer centre in South India. (24th November 2019) - Bharathi, D; Karunanidhi, G; Sethi, P; Muthukarthikeyan, M; Manivannan, M
Abstract: Background: Soft tissue sarcomas belong to a heterogeneous group of malignant tumours of mesenchymal origin which constitutes <1% of adult cancers and 12% of paediatric cancers. This study highlights the clinical spectrum of sarcomas, various histological patterns and survival outcomes. The intent is to study retrospectively the clinicopathologic profile and survival outcomes of soft tissue sarcomas and bone sarcomas treated with radiation therapy at a Regional Cancer Centre from South India. Methods: The clinical and treatment details of patients were collected retrospectively for the period 2014 -2017 and were analysed using descriptive statistics. Survival analysis was done using Kaplan-Meir Analysis. Results: The median age of presentation was 42 years (Range 2-80). Among the 123 patients studied, 54.5%(n = 67) were males and 45.5%(n = 56) were females. The most common presenting complaint was swelling 69% (n = 85) followed by pain 38.2% (n = 47). The most common site of involvement was extremity 48% (n = 59). Other more commonly involved sites were Genitourinary 7.3%(n = 9) and uterus 4.9% (n = 6). The most common histology was Ewing Sarcoma 14.6%(n = 18) followed by Undifferentiated Pleomorphic Sarcoma 13.8% (n = 17). Around 17.9%(n = 22) had metastatic disease at presentation, of which metastasis to lungs (n = 13) was most common, followed by bone (n = 8) and liver(n = 4). The intent of Radiation Therapy was Adjuvant 54.4%(n = 67), Palliative 32.2%(n = 21), Radical 13.8 (n = 17) and Neoadjuvant 6.5%(n = 8). Only 65.9%(n = 81) completed their intended radiation therapy. 91.9% (n = 113) received External Beam Radiation Therapy and 13% (n = 16) received Brachytherapy. Around 48.8% (n = 60) underwent surgery and 66.6% (n = 82) received some form of chemotherapy. The Mean Overall Survival was 50.4 months (95% CI 44.2-56.5 months). Median OS was not reached. Conclusions: As per our study, the most common histology was Ewing Sarcoma, followed by Undifferentiated Pleomorphic sarcoma. Approximately 70% of sarcoma patients referred to Radiation Oncology department were for Curative intent whereas 30% with palliative intent and this has led to Mean OS of 50.4 months. At the same time with limited follow up data and the low number of events, the Median OS was not reached. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.